2023
DOI: 10.1101/2023.10.05.23296586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling the impact of population mobility, post-infection immunity and vaccination on SARS-CoV-2 transmission in the Dominican Republic

Emilie Finch,
Eric J Nilles,
Cecilia Then Paulino
et al.

Abstract: COVID-19 epidemic dynamics are driven by a complex interplay of factors including population behaviour, government interventions, new variants, vaccination campaigns and immunity from prior infections. We aimed to quantify the epidemic drivers of SARS-CoV-2 dynamics in the Dominican Republic, an upper-middle income country of 10.8 million people, and assess the impact of the vaccination campaign implemented in February 2021 in saving lives and averting hospitalisations. We used an age-structured, multi-variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Further, a recent modeling study of SARS-CoV-2 transmission in the Dominican Republic demonstrated that the buildup of population immunity from mid-2021 increasingly limited transmission, independently affirming the role of immune restricted transmission in this setting. 19 Yet, while seemingly self-evident that individuals with higher levels of immune protection are less likely to be infected, and vice versa, without continuous infection monitoring that was not available for the current study, we are unable to unequivocally confirm this assumption. Other factors may influence or contribute to the normalization of immune markers.…”
mentioning
confidence: 60%
“…Further, a recent modeling study of SARS-CoV-2 transmission in the Dominican Republic demonstrated that the buildup of population immunity from mid-2021 increasingly limited transmission, independently affirming the role of immune restricted transmission in this setting. 19 Yet, while seemingly self-evident that individuals with higher levels of immune protection are less likely to be infected, and vice versa, without continuous infection monitoring that was not available for the current study, we are unable to unequivocally confirm this assumption. Other factors may influence or contribute to the normalization of immune markers.…”
mentioning
confidence: 60%
“…eventual reopening with exit waves of infection [157]), and hence would have underestimated the benefits of vaccination. Subsequent work found that, given the severity of the Delta variant that caused waves in mid-2021, earlier vaccination with imperfect vaccine candidates (in this case because of reduced efficacy) was preferable in terms of hospitalisations and deaths averted to waiting months for other vaccine options [165].…”
Section: Case Study 18: Vaccine Benefits Vs Risk In a Dynamic Epidemicmentioning
confidence: 99%